Absence of a measurable G2 phase in two Chinese hamster cell lines. - Liskay, R M (1977)
Evidence is presented that demonstrates the absence of a measurable G2 phase in the cell cycles of two sublines of the Chinese hamster lung fibroblast V79. One of the sublines, in addition, lacks a detectable G1 phase, thereby possessing a cell cycle comprised of simply two phases, DNA synthesis (S) and mitosis (M).